A definitive merger-AGN connection at z ∼ 0 with CFIS: mergers have an excess of AGN and AGN hosts are more frequently disturbed. Issue 2 (24th May 2019) - Ellison, Sara L; Viswanathan, Akshara; Patton, David R; Bottrell, Connor; McConnachie, Alan W; Gwyn, Stephen; Cuillandre, Jean-Charles
Abstract: The question of whether galaxy mergers are linked to the triggering of active galactic nuclei (AGN) continues to be a topic of considerable debate. The issue can be broken down into two distinct questions: (1) Can galaxy mergers trigger AGN? (2) Are galaxy mergers the dominant AGN triggering mechanism? A complete picture of the AGN-merger connection requires that both of these questions are addressed with the same data set. In previous work, we have shown that galaxy mergers selected from the Sloan Digital Sky Survey (SDSS) show an excess of both optically selected, and mid-IR colour-selected AGN, demonstrating that the answer to the first of the above questions is affirmative. Here, we use the same optical and mid-IR AGN selection to address the second question, by quantifying the frequency of morphological disturbances in low-surface brightness r -band images from the Canada France Imaging Survey (CFIS). Only ∼30 per cent of optical AGN host galaxies are morphologically disturbed, indicating that recent interactions are not the dominant trigger. However, almost 60 per cent of mid-IR AGN hosts show signs of visual disturbance, indicating that interactions play a more significant role in nuclear feeding. Both mid-IR and optically selected AGN have interacting fractions that are a factor of two greater than a mass and redshift matched non-AGN control sample, an excess that increases with both AGN luminosity and host galaxy stellar mass.